2021
DOI: 10.1002/ejic.202100015
|View full text |Cite
|
Sign up to set email alerts
|

Metal Halide Perovskites for Energy Storage Applications

Abstract: The increasing global energy demand requires the coordinated development of energy conversion and energy storage materials. Metal halide perovskites have emerged as strong semiconductor candidates for both applications. While metal halide perovskites have received much attention for a range of energy conversion devices, there is a limited use of these materials in energy storage devices. This review summarizes the current status of metal halide perovskites for Li-ion battery and supercapacitor applications whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Hybrid halide perovskites (HHPs) are the materials of the decade as tremendous progress in perovskite solar cells, perovskite light-emitting diodes, perovskite-based detectors, and memristor applications has been observed owing to their superior optoelectronic properties such as high carrier mobility, , high absorption coefficient, , ambipolar charge transport, , high quantum yield, , high color purity, excellent defect tolerance with low-temperature solution −processing, and tunable emission over a broad spectrum . Due to the mixed electronic–ionic conductivity, hybrid perovskites have also attracted attention toward energy storage applications. Ions in the perovskite materials (anions and cations) have much lower activation energies and modest ionic diffusion coefficients to move within the perovskite active layer when subjected to an external electric field or under light illumination. This feature of HHPs is a merit for energy storage applications including many switchable photovoltaic and nonvolatile memory applications. , HHPs have been used in lithium-ion batteries (LIBs), photorechargeable batteries (PRBs), and supercapacitors. ,, Ahmad et al have demonstrated two-dimensional (2D) perovskite-based efficient PRBs having capacities of up to 100 mAh g –1 . However, the typical drawbacks of LIBs and PRBs are a slow charging response time and a low power density, while capacitors have much lower energy density compared to batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid halide perovskites (HHPs) are the materials of the decade as tremendous progress in perovskite solar cells, perovskite light-emitting diodes, perovskite-based detectors, and memristor applications has been observed owing to their superior optoelectronic properties such as high carrier mobility, , high absorption coefficient, , ambipolar charge transport, , high quantum yield, , high color purity, excellent defect tolerance with low-temperature solution −processing, and tunable emission over a broad spectrum . Due to the mixed electronic–ionic conductivity, hybrid perovskites have also attracted attention toward energy storage applications. Ions in the perovskite materials (anions and cations) have much lower activation energies and modest ionic diffusion coefficients to move within the perovskite active layer when subjected to an external electric field or under light illumination. This feature of HHPs is a merit for energy storage applications including many switchable photovoltaic and nonvolatile memory applications. , HHPs have been used in lithium-ion batteries (LIBs), photorechargeable batteries (PRBs), and supercapacitors. ,, Ahmad et al have demonstrated two-dimensional (2D) perovskite-based efficient PRBs having capacities of up to 100 mAh g –1 . However, the typical drawbacks of LIBs and PRBs are a slow charging response time and a low power density, while capacitors have much lower energy density compared to batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MHP materials have also received much attention in energy storage applications due to their mixed electronic−ionic properties. [ 18,19 ] In this direction, MHP materials are used in lithium‐ion batteries (LIBs), photorechargeable batteries (PRBs), and ESCs. [ 20–22 ] Typical stumbling blocks of rechargeable batteries are slow charging rate and low power density, while capacitors have low energy density than batteries.…”
Section: Metal Halide Perovskite Supercapacitorsmentioning
confidence: 99%
“…The area capacitance of thin‐film‐based devices is in the range of μF cm −2 , as also reported in the literature. [ 18,19 ]…”
Section: Metal Halide Perovskite Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal halide perovskites (MHPs), owing to their outstanding optoelectronic properties, have emerged as an attractive class of semiconductors for single-junction and tandem solar cells, , light emitting diodes (LEDs), , photodetectors, X-ray imaging scintillators and energy storage . Particular achievement has been made in the field of perovskite solar cells (PSCs), which achieved exceptional power conversion efficiency (PCE) exceeding 25% in only a few years, approaching that of the established inorganic thin-film devices based on crystalline silicon or copper indium gallium selenide. Despite the rapid progress in the PCE of PSCs, their long-term and operational stability are still the main concerns for their practical and commercial applications. , Among the layers in the device structure, the optimization of perovskite film quality plays an essential role in overcoming the stability issues in PSCs .…”
Section: Introductionmentioning
confidence: 99%